2016
DOI: 10.1289/ehp170
|View full text |Cite|
|
Sign up to set email alerts
|

Associations between Repeated Measures of Maternal Urinary Phthalate Metabolites and Thyroid Hormone Parameters during Pregnancy

Abstract: Background:Maintaining thyroid homeostasis during pregnancy is essential for normal fetal growth and development. Growing evidence suggests that phthalates interfere with normal thyroid function. Few human studies have investigated the degree to which phthalates may affect thyroid hormone levels in particularly susceptible populations such as pregnant women.Objectives:We examined the associations between repeated measures of urinary phthalate metabolites and plasma thyroid hormone levels in samples collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 61 publications
3
62
1
Order By: Relevance
“…Previous studies of this case-control study population have characterized distributions of BPA and thyroid hormone levels by study visit of sample collection (Cantonwine et al 2015; Johns et al 2016). The overall detection rate of BPA in our study sample was 81.1%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies of this case-control study population have characterized distributions of BPA and thyroid hormone levels by study visit of sample collection (Cantonwine et al 2015; Johns et al 2016). The overall detection rate of BPA in our study sample was 81.1%.…”
Section: Resultsmentioning
confidence: 99%
“…The overall detection rate of BPA in our study sample was 81.1%. Geometric means and standard deviations for all thyroid hormones by study visit were calculated and presented in a previous study (Johns et al 2016). In Table 1., we present selected percentiles of BPA concentrations by demographic characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2015 16 observed positive correlations between MBP, MBzP, and mono(2-ethyl-5-oxohexyl) phthalate (MEOHP) and FT4 concentrations in the first trimester of gestation. A repeated measures analysis (median 10, 18, 26, and 35 weeks of gestation) 27 revealed that MEHP and mono-3-carboxypropyl phthalate (MCPP) were positively related to TT4 and FT4, respectively, whereas MEHP, mono-iso-butyl phthalate (MiBP) and MCPP were negatively associated to TSH. Therefore, these findings suggested that the direction of the associations of THs phthalates with THs phthalates varied during pregnancy 27 .…”
Section: Introductionmentioning
confidence: 99%